2022
DOI: 10.12688/hrbopenres.13548.2
|View full text |Cite
|
Sign up to set email alerts
|

What influences a person’s willingness to share health information for both direct care and uses beyond direct care? Findings from a focus group study in Ireland

Abstract: Background: The sharing of health information is invaluable for direct care provision and reasons beyond direct care, such as for health services management. Previous studies have shown that willingness to share health information is influenced by an individual’s trust in a healthcare professional or organisation, privacy and security concerns, and fear of discrimination based on sensitive information. The importance of engaging the public in policy and practice development relating to the use and sharing of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The three identified factors that shaped participants’ level of trust were: (i) their ability to exercise control over personal data that they believed belongs to them, (ii) the perceived transparency of the data sharing processes, and (iii) the perceived confidentiality of the healthcare service. This study ( Flaherty et al ., 2022 ) was part of a wider mixed methods study of national public engagement on health information carried out by the Health Information and Quality Authority (HIQA) in partnership with the Department of Health and the Health Service Executive (HSE) (2021), conducted following the Conti cyber attack ( PwC, 2021 ) on the HSE in Ireland. This mixed methods study ( HIQA, 2021 ) suggested that the Irish public is overwhelmingly in support of using health data for secondary purposes, upon the condition that appropriate safeguards are in place.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The three identified factors that shaped participants’ level of trust were: (i) their ability to exercise control over personal data that they believed belongs to them, (ii) the perceived transparency of the data sharing processes, and (iii) the perceived confidentiality of the healthcare service. This study ( Flaherty et al ., 2022 ) was part of a wider mixed methods study of national public engagement on health information carried out by the Health Information and Quality Authority (HIQA) in partnership with the Department of Health and the Health Service Executive (HSE) (2021), conducted following the Conti cyber attack ( PwC, 2021 ) on the HSE in Ireland. This mixed methods study ( HIQA, 2021 ) suggested that the Irish public is overwhelmingly in support of using health data for secondary purposes, upon the condition that appropriate safeguards are in place.…”
Section: Introductionmentioning
confidence: 88%
“…The willingness to share data was closely connected to public trust in the individual or the organisation that managed their data, and their perceived competence to keep the data safe. Trust also emerged as a major theme from a recent qualitative study that examined the factors that influenced the public’s willingness to share their health data ( Flaherty et al ., 2022 ). The three identified factors that shaped participants’ level of trust were: (i) their ability to exercise control over personal data that they believed belongs to them, (ii) the perceived transparency of the data sharing processes, and (iii) the perceived confidentiality of the healthcare service.…”
Section: Introductionmentioning
confidence: 99%
“…The willingness to share data was closely connected to public trust in the individual or the organisation that managed their data, and their perceived competence to keep the data safe. Trust also emerged as a major theme from a recent qualitative study that examined the factors that influenced the public's willingness to share their health data (Flaherty et al, 2022). The three identified factors that shaped participants' level of trust were: (i) their ability to exercise control over personal data that they believed belongs to them, (ii) the perceived transparency of the data sharing processes, and (iii) the perceived confidentiality of the healthcare service.…”
Section: Introductionmentioning
confidence: 99%
“…The three identified factors that shaped participants' level of trust were: (i) their ability to exercise control over personal data that they believed belongs to them, (ii) the perceived transparency of the data sharing processes, and (iii) the perceived confidentiality of the healthcare service. This study (Flaherty et al, 2022) was part of a wider mixed methods study of national public engagement on health information carried out by the Health Information and Quality Authority (HIQA) in partnership with the Department of Health and the Health Service Executive (HSE) (2021), conducted following the Conti cyber attack (PwC, 2021) on the HSE in Ireland. This mixed methods study (HIQA, 2021) suggested that the Irish public is overwhelmingly in support of using health data for secondary purposes, upon the condition that appropriate safeguards are in place.…”
Section: Introductionmentioning
confidence: 99%